Bidirectional Modulation of the Voltage-Gated Sodium (Nav1.6) Channel by Rationally Designed Peptidomimetics - Nolan M. Dvorak; Paul A. Wadsworth; Pingyuan Wang; Haiying Chen; Jia Zhou; Fernanda Laezza (Molecules, 2020)
Disruption of protein:protein interactions (PPIs) that regulate the function of voltage-gated Na+ (Nav) channels leads to neural circuitry aberrations that have been implicated in numerous channelopathies. One example of this pathophysiology is mediated by dysfunction of the PPI between Nav1.6 and its regulatory protein fibroblast growth factor 14 (FGF14). Thus, peptides derived from FGF14 might exert modulatory actions on the FGF14:Nav1.6 complex that are functionally relevant. The tetrapeptide Glu-Tyr-Tyr-Val (EYYV) mimics surface residues of FGF14 at the β8–β9 loop, a structural region previously implicated in its binding to Nav1.6. Here, peptidomimetics derived from EYYV (6) were designed, synthesized, and pharmacologically evaluated to develop probes with improved potency. Addition of hydrophobic protective groups to 6 and truncation to a tripeptide (12) produced a potent inhibitor of FGF14:Nav1.6 complex assembly. Conversely, addition of hydrophobic protective groups to 6 followed by addition of an N-terminal benzoyl substituent (19) produced a potentiator of FGF14:Nav1.6 complex assembly. Subsequent functional evaluation using whole-cell patch-clamp electrophysiology confirmed their inverse activities, with 12 and 19 reducing and increasing Nav1.6-mediated transient current densities, respectively. Overall, we have identified a negative and positive allosteric modulator of Nav1.6, both of which could serve as scaffolds for the development of target-selective neurotherapeutics.